2018
DOI: 10.3390/sym10110583
|View full text |Cite
|
Sign up to set email alerts
|

A Reweighted Symmetric Smoothed Function Approximating L0-Norm Regularized Sparse Reconstruction Method

Abstract: Sparse-signal recovery in noisy conditions is a problem that can be solved with current compressive-sensing (CS) technology. Although current algorithms based on L 1 regularization can solve this problem, the L 1 regularization mechanism cannot promote signal sparsity under noisy conditions, resulting in low recovery accuracy. Based on this, we propose a regularized reweighted composite trigonometric smoothed L 0 -norm minimization (RRCTSL0) algorithm in this paper. The main contributions of this paper are as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Depending on the problem size, greedy algorithms are fast and of low computational complexity. However, they are known to be sensitive to noise [45,46]. Another issue arises in the context of closely spaced radar targets, for which greedy algorithms tend to merge such targets into a single one.…”
Section: Greedy Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the problem size, greedy algorithms are fast and of low computational complexity. However, they are known to be sensitive to noise [45,46]. Another issue arises in the context of closely spaced radar targets, for which greedy algorithms tend to merge such targets into a single one.…”
Section: Greedy Algorithmsmentioning
confidence: 99%
“…The 1 -and nuclear norms are the tightest convex approximations of the 0 -norm and rank function, respectively [45,60]. However, it was found that the reconstruction error of solutions derived from convex relaxed approaches can be further reduced by applying smoothed 0 -and smoothed rank approximation frameworks [45,46,[61][62][63][64]. Their purpose is to enforce a stricter sparsity or rank measure compared to the 1 -and nuclear norm.…”
Section: Smoothed 0 -Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of electronics and information, signal processing is a hot research topic, and as a special signal, the study of image has attracted the attention of scholars all over the world [1][2][3]. In image processing, image restoration is one of the most important issues and this issue has received extensive attention in the past few decades [4][5][6][7][8][9][10][11]. Image restoration is a technology that uses degraded images and some prior information to restore and reconstruct clear images, to improve image quality.…”
Section: Introductionmentioning
confidence: 99%